2019
DOI: 10.3390/electronics8080881
|View full text |Cite
|
Sign up to set email alerts
|

SARM: Salah Activities Recognition Model Based on Smartphone

Abstract: Alzheimer's is a chronic neurodegenerative disease that frequently occurs in many people today. It has a major effect on the routine activities of affected people. Previous advancement in smartphone sensors technology enables us to help people suffering from Alzheimer's. For people in the Muslim community, where it is mandatory to offer prayers five times a day, it may mean that they are struggling in their daily life prayers due to Alzheimer's or lack of concentration. To deal with such a problem, automated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…It is evident that the age group (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) has the highest percentage (%) value of 33.71% as compared to all other defined age groups. It can also be observed that the age group (41)(42)(43)(44)(45)(46)(47)(48)(49)(50) has the second-highest rental frequency percentage (%) value of 22.34%.…”
Section: ) Rental Book Analysis Based On Rental User Age Groupmentioning
confidence: 95%
See 1 more Smart Citation
“…It is evident that the age group (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) has the highest percentage (%) value of 33.71% as compared to all other defined age groups. It can also be observed that the age group (41)(42)(43)(44)(45)(46)(47)(48)(49)(50) has the second-highest rental frequency percentage (%) value of 22.34%.…”
Section: ) Rental Book Analysis Based On Rental User Age Groupmentioning
confidence: 95%
“…The proposed architecture model of the library rental book is illustrated in figure 14. In this paper, the following ML regression models, such as DNN, SVR, and RF, have implemented in python to predict and recommend future book details [11], [49], [50]. In this section, we survey the most generally utilized metrics for the regression problem and the basic working flow of the regression models used in this paper.…”
Section: Predictive Analysis Of Rental Book Using Machine Learninmentioning
confidence: 99%
“…Recently, machine learning (ML) algorithms are widely used by the researchers to build intelligent inference models based on discovered characteristics using DM techniques to forecast time series data. ML algorithms are employed by many researchers to develop intelligent models in various domains, such as computer vision [9], business intelligence, pattern recognition [10], navigation systems [11], decision-making systems [12], etc. MLbased techniques are robust to build intelligent inference models based on historical electric consumption data and discover underlying characteristics to derive a conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…All these powerful techniques have facilitated improvement in the prediction performance of complex time-series data. ML techniques have been widely utilized in many areas, such as regression [20], classification [21], [22], patterns mining [23], [24], decision-making systems [25], [26], to name of a few. ML-based approaches tend to produce more robust predictions than conventional methods due to their ability to limit uncertainty concerning input variables having various nonlinear dependencies to generate accurate and reliable predictions.…”
Section: Introductionmentioning
confidence: 99%